Balancing Child Education and Parental Care: The Sandwich Generation from an Islamic Education Perspective - Imel Putri Dewita; Goestina (Jurnal Educative: Journal of Educational Studies, 2026)
The "sandwich generation" confronts multidimensional pressures in balancing modern employment with the dual responsibilities of eldercare and child-rearing. While secular literature heavily frames this as a structural crisis leading to caregiver burnout, empirical studies within the framework of Islamic education remain scarce. This qualitative study explores how working mothers negotiate these role conflicts by actualizing Islamic educational values as a "lived religion." Employing a descriptive-analytical design, data were collected through in-depth interviews and observations with 13 working mothers of Nasyiatul 'Aisyiyah in Takalar Regency. The findings reveal three main themes. First, participants face severe structural vulnerabilities driven by systemic financial strain and time scarcity. Second, rather than succumbing to burnout, they cognitively reconstruct this dual burden into a divine trust (Amanah). The domestic sphere is utilized as a multidimensional worship space, integrating Birrul Walidain (filial piety) with Tarbiyah bil Qudwah (education through role modeling). Third, Islamic values Ikhlas (sincerity), Sabr (patience), Tawakkul (reliance on God), and Syukr (gratitude) are operationalized as active psycho-spiritual mechanisms, functioning as a mental shield against economic anxiety and emotional spillover. This study concludes that Islamic spiritual resilience challenges secular paradigms of inevitable caregiver exhaustion. These findings contribute to a contextual understanding of how Islamic educational values support role negotiation among working mothers within the Nasyiatul 'Aisyiyah community in Takalar Regency. They also provide an empirical reference for developing family education and counseling programs in similar Muslim community organizations, rather than proposing a universally applicable model.